Higher Education, Exclusion, and Belonging: Religious Complexity, Coping and Connectedness Among International Students During the COVID-19 Pandemic in Australia - Weng, Enqi; Halafoff, Anna; Barton, Greg; Smith, Geraldine (Journal of International Students, 2021)
Generations of migrants from Asia since the 1800s have endured challenges in locating their place and belonging in Australia due to systemic racism and discrimination against the cultural and religious ‘other’. These persistent issues have intensified during the pandemic, especially towards Chinese communities, including international students. This paper investigates the impact of the pandemic on Chinese, Indian and Russian international students in Australia. It reveals how, throughout the first year of the pandemic, international student, ethnic and religious community organizations implemented multiple and overlapping coping strategies to assist international students in Australia, who had been left vulnerable by a lack of government support and escalating geopolitical tensions in the Asia-Pacific region. By highlighting the religious dimensions of these strategies of connectedness and belonging, it contributes new insights in an under-explored aspect in studies on international students in Australia, pointing the way for further investigation.